PENGARUH ENVIRONMENTAL PERFORMANCE DAN ENVIRONMENTAL DISLOSURE TERHADAP FINANCIAL PERFORMANCE - Anthony Holly; Ana Mardiana; Robert Jao; Paulus Tangke; Imelda The (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2023)
The purpose of this study is to analyze the effect of environmental performance and environmental disclosure on financial performance. This type of research is causality research that builds a causal relationship between the independent variables and the dependent variable. The main theories used in this research are Legitimacy Theory and Stakeholder Theory. The population used in this study are all non-financial companies listed on the Indonesia Stock Exchange (IDX) with the research period 2018-2020. The number of research samples is 15 companies selected by purposive sampling method and using secondary data, namely annual reports, PROPER results, and company sustainability reports. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that environmental performance has a positive and significant influence on financial performance. This study also shows that environmental disclosure has a positive and significant effect on financial performance.